(untitled) - Froyen, Richard T. (Upper Saddle River, NJ., 2005)
In this new edition of a standard text, discussion includes a summary of the Keynesian position and a detailed analysis of the challenges to it, an extensive treatment of monetary policy, and a consideration of the determinants of long-run economic growth. Coverage of questions of measurement is followed by discussion of major macroeconomic models, open economy macroeconomics, macroeconomic policy, and extensions of macroeconomic models.
Keywords: Macroeconomics,Keynesian economics